Accurate determination of bubble size and expansion ratio for polymer foaming with non-isothermal PBB model based on additional energy conservation. (15th March 2022) - Ge, Yukai; Fang, Zhiying; Liu, Tao
Highlights: A non-isothermal pressure-balanced bubble-growth (PBB) model was established. The gas expansion work and internal energy change were investigated. The model could accurately predict the bubble size and expansion ratio. Effects of molecular structure and viscoelasticity on internal energy and bubble growth were available. Gas efficiency of the foaming agent was defined to evaluate its economic feasibility. Abstract: A non-isothermal pressure-balanced bubble-growth (PBB) model has been proposed based on mass, momentum and energy conservation, which additionally considered the decrease in the internal energy of gas due to the work done by gas expansion in bubble. The model could accurately predict the bubble size and expansion ratio for the melt foaming of four polymers for a wide range of cell densities from 1.5 × 10 13 to 1.9 × 10 15 cells/m 3 . Furthermore, the simulation results indicate that the bubble shell resisted bubble growth and consumed significant energy, preventing the growth of some small nucleations. During the melt foaming process, the energy cost of the linear polymer is continuously kept at a high level, which reduces the bubble size, while that of the long-chain branched polymer attenuates fast, thereby increasing the expansion ratio. Finally, we defined the gas efficiency of the foaming agent to evaluate the economic feasibility of the foaming agent in foaming processes.